1986
DOI: 10.1017/s0305004100064410
|View full text |Cite
|
Sign up to set email alerts
|

Lindelöf locales and realcompactness

Abstract: We show that a locale possesses the localic analogue of the property of realcompactness if and only if it is regular Lindelöf. Thus, the localic version of the Hewitt real-compactification, originally defined by G.Reynolds using σ-frames, is the regular Lindelöf reflection. An immediate consequence is that a space is realcompact if and only if it is the point space of a regular Lindelöf local (3·2). We point out a nice analogy between a theorem of Reynolds and Stone's classical representation theorem for boole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 9 publications
(14 reference statements)
0
38
0
Order By: Relevance
“…In [9] it is shown that H and Coz induce an equivalence between the categories LRegFrm (regular Lindelöf frames) and RegσFrm.…”
Section: Preliminariesmentioning
confidence: 99%
“…In [9] it is shown that H and Coz induce an equivalence between the categories LRegFrm (regular Lindelöf frames) and RegσFrm.…”
Section: Preliminariesmentioning
confidence: 99%
“…Using localic language, Madden and Vermeer [15] have shown that regular Lindelöf locales form a reflective subcategory of the category of locales by actually constructing the reflection, λL, for any completely regular locale L. We recall the construction in frame terms because that is the category of discourse in this paper.…”
Section: The Coreflections βL λL and υLmentioning
confidence: 99%
“…The regular Lindelöf coreflection of L, denoted λL, is the frame of σ -ideals of Coz L (see [15]). The frame υ L is constructed in the following manner.…”
Section: Real and Hyper-real Ideals Of Rlmentioning
confidence: 99%